2019
DOI: 10.3390/w11102083
|View full text |Cite
|
Sign up to set email alerts
|

Additional Value of Using Satellite-Based Soil Moisture and Two Sources of Groundwater Data for Hydrological Model Calibration

Abstract: Although the complexity of physically-based models continues to increase, they still need to be calibrated. In recent years, there has been an increasing interest in using new satellite technologies and products with high resolution in model evaluations and decision-making. The aim of this study is to investigate the value of different remote sensing products and groundwater level measurements in the temporal calibration of a well-known hydrologic model i.e., Hydrologiska Bryåns Vattenbalansavdelning (HBV). Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Other studies combined soil moisture and groundwater observations at the point (Carrer et al, 2019) or large (i.e. remote sensing) (Demirel et al, 2019;Nijzink et al, 2018) scale to characterise catchment-scale storage. Overall, our approach is complementary to these others as some sort of SWC data transformation specific to the study site remains a requirement for catchment storage characterisation.…”
Section: To What Extent Is Near Surface Storage Coupled To Catchment-scale Storage and Discharge Dynamics?mentioning
confidence: 99%
“…Other studies combined soil moisture and groundwater observations at the point (Carrer et al, 2019) or large (i.e. remote sensing) (Demirel et al, 2019;Nijzink et al, 2018) scale to characterise catchment-scale storage. Overall, our approach is complementary to these others as some sort of SWC data transformation specific to the study site remains a requirement for catchment storage characterisation.…”
Section: To What Extent Is Near Surface Storage Coupled To Catchment-scale Storage and Discharge Dynamics?mentioning
confidence: 99%
“…Previous studies used ground‐based or alternatively remote sensing products or their combination as such additional information on hydrologic processes. Soil moisture (Kundu et al, 2017; Kunnath‐Poovakka et al, 2016; Parajka et al, 2006; Rajib et al, 2016; Shahrban et al, 2018), evapotranspiration (Gui et al, 2019; Herman et al, 2018; Immerzeel & Droogers, 2008; Kunnath‐Poovakka et al, 2016), and groundwater level data (Demirel et al, 2019; Seibert, 2000) were often used for model calibration to improve the model's internal consistency. These studies showed the added value of different observations besides runoff, for example, for soil moisture, evapotranspiration, and groundwater levels.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, radar penetration does not exceed a 5 cm soil top layer [22]. SM's sensitivity to maximum storage capacity has already been reported, although not fully assessed for many soil types [62]. Soil water storage, S, is assumed to correspond to a constant moisture value throughout the soil profile.…”
Section: Effect Of Smaxmentioning
confidence: 99%
“…Despite these constraints, satellite products have a large potential for assessing terrestrial water balance dynamics and for understanding their spatial and temporal variability at multiple scales [18]. Most studies referenced above used hydrological modelling based on water balance approaches applied at large spatial scales and a common conclusion was that the joint assimilation of soil moisture and total water storage remote data improves model performance [60][61][62]. Furthermore, the validation of radar products is commonly performed with meteorological data matrices that are obtained from satellite data, such as NOOA or Meteosat (e.g., [18,[60][61][62][63][64][65]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation